Assessment of age-related influences on the quality of life of breast cancer patients before and after surgical treatment - Kostić, Sanja; Murtezani, Zafir; Andrić, Zoran; Ivanović, Nebojša; Kozomara, Zoran; Kostić, Marko; Miličić, Vesna; Kocić, Sanja (Vojnosanitetski pregled, 2021)
Background/Aim. Breast cancer comprises about 25% of all female cancers, and its incidence is increasing. New diagnostic procedures and therapeutic modalities have increased treatment success rates as well as patient survival. The goal of contemporary treatment is not only patient survival, but also a better quality of life (QoL). The objective of this study was to assess the effect of age at diagnosis on the QoL of patients with breast cancer before and after surgery. Methods. We analyzed QoL in 170 female patients (43 patients < 50 and 127 patients ≥ 50 years) diagnosed with breast cancer (I and II stage) a month before and after surgical treatment, using the European Organisation for Research and Treatment of Cancer (EORTC QLQ-C30) questionnaire and specific version for breast cancer patients (EORTC QLQ-BR23). Results. The QLQ-C30 questionnaire showed that surgical treatment significantly decreased all domains of the patients’ QoL in both age groups. Age-related differences were present in sexual functioning and pleasure independently of surgical treatment, with higher scores in the group of younger women. The analysis of data obtained using the QLQ-BR23 questionnaire revealed a lower QoL after surgical treatment in almost all dimensions regardless of patients’ age. Conclusion. The results of our study pointed out statistically significant differences in the QoL domains of sexual functioning, and sexual enjoyment between women in both age groups independently of surgical treatment. The QoL was better in the younger age group. Surgical breast cancer treatment negatively affected patients QoL independently of age.
Keywords: breast neoplasms; quality of life; age groups; surgical procedures, operative; surveys and questionnaires